The Impact of Financial Inclusion and Financial Literacy on Improving People's Economic Welfare in Indonesia - Judijanto, Loso; Novitasari, Salwa Aulia; Arini, Rani Eka (Westscience Press, 2025)
This study examines the impact of financial inclusion and financial literacy on improving the economic welfare of communities in Indonesia using a quantitative analysis approach. Data were collected from 70 respondents through a structured questionnaire employing a 1–5 Likert scale, and the relationships between variables were analyzed using Structural Equation Modeling - Partial Least Squares (SEM-PLS) with SmartPLS 3 software. The results demonstrate that financial inclusion significantly enhances economic welfare by increasing access to formal financial services and promoting financial stability. Financial literacy also positively affects economic welfare by equipping individuals with the knowledge and skills to make informed financial decisions. Moreover, the synergistic effect of financial inclusion and financial literacy produces the most substantial improvements in economic welfare, highlighting the need for integrated policies. These findings provide theoretical and practical implications, suggesting that policymakers should prioritize comprehensive strategies that combine access to financial services with financial education to foster sustainable economic development.